2016
DOI: 10.1159/000448039
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Streptococcus pyogenes</i></b> Escapes Killing from Extracellular Histones through Plasminogen Binding and Activation by Streptokinase

Abstract: Histones are small basic proteins and highly conserved among eukaryotes. Their main function is binding, packaging and organizing of DNA in the nucleus, but extracellular histones are also potent antimicrobial proteins. Here we found that Streptococcus pyogenes - an important human pathogen - protects itself from histone-killing by the acquisition of plasminogen. Plasminogen, bound to the streptococcal surface, efficiently prevents histone-mediated killing. Moreover, the streptokinase/plasminogen complex degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…GAS infection studies in animals have provided strong evidence that GAS has the ability to manipulate the host fibrinolytic system at many levels [88,89]. On one hand, hijacking the host Plg/Plm on the bacterial surface has provided an energy-efficient strategy to break down the fibrin network during dissemination [55,57,90], and this is achieved with the aid of PAM. Using GAS strains which express both SK2b and PAM genes, it was shown that inactivation of either genes significantly reduces virulence [59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAS infection studies in animals have provided strong evidence that GAS has the ability to manipulate the host fibrinolytic system at many levels [88,89]. On one hand, hijacking the host Plg/Plm on the bacterial surface has provided an energy-efficient strategy to break down the fibrin network during dissemination [55,57,90], and this is achieved with the aid of PAM. Using GAS strains which express both SK2b and PAM genes, it was shown that inactivation of either genes significantly reduces virulence [59].…”
Section: Resultsmentioning
confidence: 99%
“…All invasive GAS strains express SK to enhance dissemination [55,56] and colonization within the host [57]. Interestingly, the SK alleles are polymorphic and can be subdivided into two phylogenetic lineages based on the highly variable β domain [38], namely, cluster 1 (SK1) and cluster 2 (SK2) (Figure 4a) [38,58,59].…”
Section: Classification Of Streptokinasementioning
confidence: 99%
“…S. pyogenes, also known as group A Streptococcus, is a Grampositive bacterium for which the bactericidal action of histones has been previously demonstrated (34,35). Thus, we asked whether soluble FnBPB(163-480) could competitively neutralize the bactericidal activity of H3 for this bacterium.…”
Section: Interactions Of Histones With S Aureus Fnbpbmentioning
confidence: 99%
“…In a study by Nitzsche et al (34), S. pyogenes serotype M49 has been shown to protect itself from histone-killing through PLG acquisition and activation by streptokinase. However, the question was not addressed whether the M49 protein is directly involved in PLG and/or histone binding (34).…”
Section: Interactions Of Histones With S Aureus Fnbpbmentioning
confidence: 99%
See 1 more Smart Citation